Analisis Hukum Normatif UUNo 32 Tahun 2002Mengenai Peran KPI Sebagai Lembaga PelayananPublik Dalam Hal Pengawasan Penyiaran di Indonesia - Syukri, Muhammad (UNES Law Review, 2024)
Indonesian broadcasting Commission is an Independent public departmen, which established for holding the regulation, supervision, and law enforcement toward national broadcast departmen. Beside, that Indonesia Broadcasting Commission role, also directed for supporting govermment’ts duty in educating the nation toward broadcasting. This expectation appropriate to Indonesian national broadcasting purposes which’s included in law number 32 year 2002 aboaut broadcasting.The role of Indonesian Broadcasting Commission in ordor to support government’s duty in educating the nation through broadcasting is by making broadcasting regulation. Supervision and law enforcement are for the violations of broadcasting regulation. Indonesian Broadcasting Commission’s role is expected in order to supervise the broadcasting and together provide protection to the Indonesian society, so that indonesian society can enjoy national broadcasting which enlightens, nurture and educate. So That, national broadcasting purposes which’s mandated by Law number 32 year 2002t about broadcasting can be achieved.